Effect of thin layer drying conditions on the retention of bioactive components in Malabar spinach (Basella alba) leaves - Gulshan Kumar; Jayasree Joshi T; Pavuluri Srinivasa Rao; Padmavati Manchikanti (Food Chemistry Advances, 2023)
Malabar spinach (Basella alba) is an underexploited tropical leafy vegetable with high nutritional value and therapeutic properties. The leaves are rich in polyphenols, flavonoids, and antioxidants. Identifying appropriate drying methods and conditions for B. alba leaf production and storage can stimulate large-scale manufacture while preserving its intrinsic bioactive components. In this study, an investigation has been carried out to study the impact of thin-layer drying conditions on the retention of bioactive components in B. alba leaves. Drying tests were performed in a hot air oven (50, 60, 70 °C), microwave (600, 650, 700, 750,800 W), and freeze dryer (freezing temperature: -35 °C and vacuum pressure:150 mbar). The drying characteristics of the leaves were investigated. Semi-empirical thin-layer drying models were fitted to the obtained data with the intent to predict the drying behaviour of leaves. Amongst the fitted models, Page and Aghbashlo models showed the best performance with a high R2 value (0.98 – 0.99). The total drying time taken for microwave drying was 98.25% less than the hot air oven drying and 99.19% less than freeze drying. Maximum retention of total phenolic (4.80 ± 0.12 mg GAE g−1) and total flavonoid (5.95 ± 0.02 mg GAE g−1) compounds was observed in freeze-dried samples. Microwave dried samples showed high antioxidant activity than other samples due to less processing time. Results also revealed a less activation energy of 2.22 kJ mol−1 for microwave drying with high moisture diffusivity (1.54 × 10–9 to 4.09 × 10–9 m2s−1).